Dual‐Phase Engineering of Nickel Boride‐Hydroxide Nanoparticles toward High‐Performance Water Oxidation Electrocatalysts. (21st July 2020) - Hong, Yu‐Rim; Kim, Kang Min; Ryu, Jeong Ho; Mhin, Sungwook; Kim, Jungin; Ali, Ghulam; Chung, Kyung Yoon; Kang, Sukhyun; Han, HyukSu
Abstract: The development of earth‐abundant and efficient oxygen evolution reaction (OER) electrocatalysts is necessary for green hydrogen production. The preparation of efficient OER electrocatalysts requires both the adsorption sites and charge transfer on the catalyst surface to be suitably engineered. Herein, the design of an electrocatalyst is reported with significantly enhanced water oxidation performance via dual‐phase engineering, which displays a high number of adsorption sites and facile charge transfer. More importantly, a simple chemical etching process enables the formation of a highly metallic transition boride phase in conjunction with the transition metal hydroxide phase with abundant adsorption sites available for the intermediates formed in the OER. In addition, computational simulations are carried out to demonstrate the water oxidation mechanism and the real active sites in this engineered material. This research provides a new material design strategy for the preparation of high‐performance OER electrocatalysts. Abstract : A novel material design concept of dual‐phase engineering is developed via facile chemical etching toward a highly efficient and robust oxygen evolution reaction electrocatalyst. High number of adsorption sites and facile charge transfer are simultaneously secured through the dual‐phase engineering concept.